Cognitive differences between older adult instrumental musicians: Benefits of continuing to play. (January 2020) - Strong, Jessica V.; Midden, Allison
Previous research suggests that ongoing cognitive engagement in late life may help maintain cognitive functioning. We assessed cognition across all major domains in older adult instrumental musicians (active vs. former) and non-musicians using a standardized neuropsychological battery and collected self-report information on levels of physical activity, social activity, and overall health. We used ANCOVAs to determine if there were differences in cognitive test scores among groups. Results showed that all musicians (active and former) had higher scores on a test of language (Boston Naming Test) and of language and executive functioning (Controlled Oral Word Association) compared to non-musicians. However, active musicians scored higher than both non-musicians and former musicians on a version of the Stroop task (Delis-Kaplan Executive Function System: Color Word Interference). These findings suggest that, in some types of executive functions, there may be continued benefit to participating in musical activities later in life. However, in the domain of language, gains from playing an instrument are sustained even if a musician stops playing. We discuss these results in the contexts of cognitive reserve and crystallized and fluid intelligence, including cognitive benefits of early life music lessons that remain in late life.